Effect of PAIP1 on the metastatic potential and prognostic significance in oral squamous cell carcinoma - Neeti Swarup; Kyoung-Ok Hong; Kunal Chawla; Su-Jung Choi; Ji-Ae Shin; Kyu-Young Oh; Hye-Jung Yoon; Jae-Il Lee; Sung-Dae Cho; Seong-Doo Hong (Nature Publishing Group, 2022)
Abstract Poly Adenylate Binding Protein Interacting protein 1 (PAIP1) plays a critical role in translation initiation and is associated with the several cancer types. However, its function and clinical significance have not yet been described in oral squamous cell carcinoma (OSCC) and its associated features like lymph node metastasis (LNM). Here, we used the data available from Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA), and Clinical Proteomic Tumor Analysis Consortium (CPTAC) to analyze PAIP1 expression in oral cancer. The publicly available data suggests that PAIP1 mRNA and protein levels were increased in OSCC. The high PAIP1 expression was more evident in samples with advanced stage, LNM, and worse pattern of invasion. Moreover, the in vitro experiments revealed that PAIP1 knockdown attenuated colony forming, the aggressiveness of OSCC cell lines, decreasing MMP9 activity and SRC phosphorylation. Importantly, we found a correlation between PAIP1 and pSRC through the analysis of the IHC scores and CPTAC data in patient samples. Our findings suggest that PAIP1 could be an independent prognostic factor in OSCC with LNM and a suitable therapeutic target to improve OSCC patient outcomes.